Single Page Lesson Plan Model for Crisis Learning Era - Maulana, Riyan; Farsia, Lina; Kholid, Mohammad (English Education Journal, 2024)
Curriculum changes for improvement are being pursued to achieve optimal results, with the latest policy requiring teachers to create single-page lesson plan. The spread of COVID-19 in Indonesia has necessitated that teachers adapt lesson plan to current environmental conditions. The single-page lesson plan is suitable as a model for online learning because it is concise, practical, and consists of only one page. This policy has drawn attention from various parties, particularly English teachers, as it is a new approach and poses challenges in the teaching process. A lesson plan must include components such as identity, learning objectives, systematic learning activities, learning methods and media used, learning resources, and the time needed. These components are essential as a guide for teachers to conduct lessons as planned. Single-page lesson plan created by teachers are expected to accommodate students’ conditions and the specific characteristics of the subjects being taught, with English as the subject highlighted here. The research model used is the Plomp Model (2013), which consists of three stages: the initial assessment (preliminary research), the design stage (prototype phase), and the final assessment phase (assessment phase).